MENINGKATKAN KUALITAS PEMBELAJARAN MATEMATIKA TENTANG NILAI TEMPAT - F. T. Munthe (Perspektif Ilmu Pendidikan, 2008)
This class action research aims at overcoming the problems in learning place value in mathematics and improving the student’s learning achievement. This action research was conducted in grade 3 of Government Primacy School, Jati 03 (Morning), East Jakarta. The research model adopted Kemmis and Mc Taggart’s with four steps (Planning, Implementation, Observation, and Reflection). Within three cycles, it was discovered the effectiveness of teaching aids in improving the student’s learning achievement in studying place value in mathematics.